Trade-off between Utility and Security using Group Privacy Threshold Sanitization - Cynthia Selvi, P; Mohamed Shanavas, AR (International Journal of Computer Sciences and Engineering, 2014)
Data mining is a well-known technique for automatically and intelligently extracting useful information or knowledge from a large amount of data, but it can also disclose sensitive information of an individual or a company. This promotes the need for privacy preserving data mining which is becoming an increasingly important field of research and many researchers have proposed techniques for handling this concept. However, most of the privacy preserving data mining approaches concentrate on fixed disclosure threshold strategy for all sensitive information. This article proposes an approach for group-based threshold strategy which may help facilitate to use varying sensitivity level for the information to be hidden.